2023
DOI: 10.1111/bph.16009
|View full text |Cite
|
Sign up to set email alerts
|

Soluble epoxide hydrolase inhibition enhances production of specialized pro‐resolving lipid mediator and promotes macrophage plasticity

Abstract: Background and Purpose: Epoxyeicosatrienoic acids (EETs) and other epoxy fatty acids (EpFA) are lipid mediators that are rapidly inactivated by soluble epoxide hydrolase (sEH). Uncontrolled and chronic inflammatory disorders fail to sufficiently activate endogenous regulatory pathways, including the production of specialized proresolving mediators (SPMs). Here, we addressed the relationship between SPMs and the EET/sEH axis and explored the effects of sEH inhibition on resolving macrophage phenotype.Experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 74 publications
0
15
0
Order By: Relevance
“…Three of the 399 identified activators (Table 1, entries 1-3) shared a common benzothiazole phenylsulfonyl-piperidine carboxamide (BT-PSP) core structure. To determine if this series of benzothiazoles might serve as a tractable lead for the development of activators as chemical probes, we obtained additional structurally similar compounds using a combination of targeted purchasing of commercial molecules (Table 1, entries 4-13) and discrete chemical synthesis (Table 1, entries [14][15][16][17][18][19][20][21][22]. The activity of this series of 22 benzothiazole phenylsulfonyl-piperidine carboxamides thus obtained was assessed for enzyme activation using recombinant mouse Nape-pld (Supplemental Figure 1 and Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Three of the 399 identified activators (Table 1, entries 1-3) shared a common benzothiazole phenylsulfonyl-piperidine carboxamide (BT-PSP) core structure. To determine if this series of benzothiazoles might serve as a tractable lead for the development of activators as chemical probes, we obtained additional structurally similar compounds using a combination of targeted purchasing of commercial molecules (Table 1, entries 4-13) and discrete chemical synthesis (Table 1, entries [14][15][16][17][18][19][20][21][22]. The activity of this series of 22 benzothiazole phenylsulfonyl-piperidine carboxamides thus obtained was assessed for enzyme activation using recombinant mouse Nape-pld (Supplemental Figure 1 and Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In macrophages, the pharmacological inhibition of soluble epoxide hydrolase stimulated a dynamic transcriptional reprogramming of inflammatory macrophages toward resolving macrophages (characterized by CD11c + /CD206 + double-positive cells in the CD45 + /CD11b + /CD64 + macrophage population), associated with reduced expression of Il1β, TNFα, Il12, and Nos2. Finally, in vitro assay revealed that sEH inhibition and EET treatment triggered SPM release in bone marrow derived macrophages (BMDMs) in both inflammatory and resolvents macrophages (23). These findings are summarized in Figure 2.…”
Section: Inhibition Of Soluble Epoxy Hydrolase In Periodontal Tissues...mentioning
confidence: 87%
“…The pharmacological inhibition of soluble epoxide hydrolase and its impact on inflammatory, autoimmune, and pain disorders has been widely explored (63)(64)(65)(66). Nevertheless, its application in periodontitis or other orofacial conditions is new (18,(21)(22)(23)67). There are only a few studies involving the inhibition of the soluble epoxide hydrolase enzyme in periodontal disease (21-23); therefore, we will address them in detail.…”
Section: Inhibition Of Soluble Epoxy Hydrolase In Periodontal Tissues...mentioning
confidence: 99%
See 2 more Smart Citations